Effect of different angles of knee flexion on leg extensor power in healthy individuals. - Barker, K; Crystal, C; Newman, M (2012)
OBJECTIVES: To investigate the effect of fixed flexion knee deformity on leg extensor power as measured by the Nottingham leg extensor power rig. DESIGN: Cross-sectional observational study. SETTING: Orthopaedic hospital. PARTICIPANTS: A convenience sample of 135 adult participants. MAIN OUTCOME MEASURES: leg extensor power normalised for body weight, UCLA activity scale. RESULTS: Power values at 0° FF were found to be significantly less than power values at 15° FF [difference 0.21W/kg SD .36], and power values at 15° FF were significantly less than those at 30° FF [difference 0.31W/kg SD .43; P<0.001) in both right and left legs. Age and activity levels were moderately negatively correlated, with UCLA score decreasing with increasing age (-0.343, P<0.0005). No significant correlation was found between activity levels measured on the UCLA and power on the LEP. CONCLUSIONS: Given the large range of pre-operative maximal extension, the validity of testing each patient at their own maximal range of pre-intervention extension and then at the same angle post-intervention is questionable. In studies assessing change in power following an intervention, the end point angle should be standardised between individuals. In future studies investigating leg extensor power on the LEP rig pre and post intervention, it could be more appropriate to standardise the angle of FF to 30°, with individuals who are unable to achieve this position excluded from the study.